Model of innovative development of a construction enterprise (Economics and region, 2024)
The purpose of the article is to study the theoretical and applied aspects of innovation activity and to form an innovative model of development of a construction enterprise. The full-scale war in Ukraine has caused significant difficulties, risks and challenges to the country's economic sustainability. During this difficult period, the issue of innovative development of an enterprise in the face of challenges and threats, as well as a tough competitive environment, is relevant, as it requires businesses to build a sustainable position in the relevant product market. This, in turn, requires flexibility and innovation in business decisions. The author argues that it is necessary to form a stable position in the relevant commodity market, which implies flexibility and innovation in business decisions. This is due to the difficult period of doing business on an innovative basis in the face of challenges and threats caused by the full-scale war in Ukraine. The results of research by many scientists and experts on the essence of innovation have allowed us to offer the author's vision of the category “innovation” as the final result of innovation activity, which is an improved organizational, managerial, technological and marketing process to achieve economic, social and environmental benefits. The methodology of T. Burmak is applied to assess the innovative potential of enterprise on the basis of materials of LLC “Technobud-Ukraine”. A comprehensive analysis of the enterprise is carried out by thirteen indicators that reflect the real state of its development. The evaluation was carried out by the expert method. Each indicator is evaluated on a scale from 0 to 10. The analysis is based on organizational, managerial, production and market indicators. The calculated value for Technobud-Ukraine LLC is 3.78 and corresponds to a low level of innovation and investment potential. Low innovation activity is typical for most construction companies in the world. They are not very prone to innovation, which is quite objective. The inertia of construction companies is caused by several factors. First, it is the long period of operation of buildings and structures, during which the shortcomings of the technology used may become apparent. This makes construction companies very cautious when choosing new materials and construction methods. Secondly, builders are highly responsible for the final result, as the use of inappropriate technology or design errors can endanger the lives of many people. However, the situation has changed significantly over the past decade due to a number of factors. The conservative construction industry is likely to be forced to abandon its established traditions and make a number of radical changes. The rapid introduction of computer-aided information modeling at all key stages of the construction cycle and other advanced IT technologies has already had a significant impact on the industry. Over the next few decades, the very set of materials and technologies used in construction may change dramatically. Taking into account the above, we have built a Model of Innovative Development of a Construction Enterprise aimed at strengthening competitiveness. The model is designed not only for construction companies, but is also adapted to other enterprises of the real sector of the economy, and provides for the examination of priority areas of innovation, assessment of the innovative potential of the enterprise, availability of methodological tools, formation of an information environment and information support for making a positive decision.
Keywords: innovative potential; innovative development model; construction enterprise; innovative investment portfolio; innovative project